Apatite coatings on chemically modified titanium using a new accelerated biomimetic route - Morejon-Alonso, Loreley; Bussulo, Mauricio A.; Debone, Rodolfo [UNESP]; Gonzalez-Martinez, Eduardo; Gonzalez, Jesus E. (Elsevier B.V., 2020)
To improve the osseointegration and biological performance of biomedical titanium, hydroxyapatite (HA) was coated onto chemically modified titanium (Ti) using a novel and fast biomimetic route which incorporated supersaturated calcification solutions (SCS). As a result, it is possible to obtain HA coatings on both acid and base chemically-modified titanium surfaces within 2 h using SCS. After coating, acid etched and heat treated Ti exhibited a fine and homogenous coating of hydroxyapatite crystals that did not change morphology after 4 h. Alkaline-modified Ti showed a denser and thicker nano-sized hydroxyapatite layer (particle size about 100 nm) at 2 h due to the presence of hydrogen sodium titanate. Therefore, no heat treatment was necessary to induce HA precipitation. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Titanium; Hydroxyapatite; Biomimetic; Supersaturated calcification solutions